Training evaluation based on the Kirkpatrick Model and Kemp Model using SEM-PLS: A case study of training for expenditure treasures in DKI Jakarta Province - Radite Handalani; Hari Soesanto (Monas: Jurnal Inovasi Aparatur, 2022)
This study aims to analyze the training evaluation of the Kirkpatrick model and the Kemp model for Expenditure Treasurer Training at the Provincial Government of DKI Jakarta. This study found a comprehensive analysis of all aspects of training management resources suggested to be determinants of training quality, participant scores, participant utilization, and competency testing. All elements are involved in the four levels of Kirkpatrick's Training Evaluation, starting from Reaction, Learning, Behavior, and Outcomes. The method used in this study uses Structural Equation Modeling Partial Least Square (SEM-PLS) using the SmartPLS Version 3.0 application, which can produce a reliable and robust model. Analysis of the 780 respondents in this study used the census method involving sub-variables and aspects of training quality, increasing participant scores, participant utilization, and competency tests described in 14 research findings. This research produced the best model using Re-sampling and Bootstrapping methods and various in-depth analyses.